Beyond the Bauhaus Cultural Modernity in Breslau, 1918-33 - Ascher Barnstone, Deborah (University of Michigan Press, 2016)
The Breslau arts scene during the Weimar period was one of the most vibrant in all of Germany, yet it has disappeared from memory and historiography. 'Beyond the Bauhaus' explores the polyvalent and contradictory nature of cultural production in Breslau in order to expand the cultural and geographic scope of Weimar history.